Food Bioactives Extraction and Biotechnology Applications - Puri, Munish; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on various types of bioactive compounds, including secondary metabolites, oligosaccharides, polysaccharides, flavonoids, peptides/proteins, carotenoid pigments, quinones, terpenes, and polyunsaturated fatty acids, and presents an overview of their nutraceutical activities. It covers the current status and future potential of food compounds, as well as extraction technologies for biaoctives derived from plant, fungi and marine-derived bioactive agents. Finally, health-promoting effects of plant, fungi and marine-derived bioactive agents are discussed. Chapters come from top researchers in this area from around the globe. The volume caters to the needs of undergraduate and post-graduate students in the area of food biotechnology, food bioprocessing, biotechnology, food engineering, etc., and also contains information pertinent to researchers. .
Preface -- 1. Glucosinolates & respective derivatives (isothiocyanates) from Plants -- 2. Bioactives from mushroom and their application -- 3. Bioactive Products from Fungi -- 4. Process Development for Bioactive Peptide Production -- 5. Comparison of Natural Extraction and Recombinant Mussel Adhesive Protein Approaches -- 6. Extraction of lipids and carotenoids from algal sources -- 7. Magnetic particles for microalgae separation and biotechnology -- 8. Enzyme assisted extraction of bioactives -- 9. Emerging technologies for bioactive applications in foods -- 10. Emerging Technologies of Hydrogels in Bioactive Compounds Delivery -- 11. Neurocognitive improvement through plant-food bioactives: a particular approach to Alzheimer's disease -- 12. Multifunctional Bioactives for Cancer Therapy: Emerging Nano-Sized Delivery Systems -- Index.
Keywords: Food science; Food -- Microbiology; Biotechnology; Food Science; Food Microbiology; Biotechnology